PREVENTING HYPOTENSION CAUSED BY SPINAL ANESTHESIA IN NON PREECLAPMTIC PREGNANCIES WITH CAESAREAN SECTION - Radhitya, I Gusti Agung Ngurah; Pratama, Razi Ageng (Lux Mensana: Journal of Scientific Health, 2023)
Introduction. Caesarean method widely used and become popular among pregnant women. In general, this method mostly used regional anesthesia (spinal, epidural and CSE). However, many reports incidence of complication related to spinal anesthesia after the procedure. Maternal hypotension is the most common complication after spinal anesthesia procedure. Therefore, anesthesiologist need to prevent hypotension during spinal anesthesia in caesarean section. Method. The researcher examines several scientific journals from PubMed, BJA, Elsevier, Cochrane Library and BMC research until 10th August, 2023 for abstracts, conference proceedings, and full-text papers that evaluated prevention of hypotension in non-preeclampsia patients undergoing caesarean delivery under spinal anesthesia. In addition, the researchers examine the research conducted during 2016 to 2023. Result & Analysis. The researchers examine 28 scientific article (11.153 parturient) with 6 different methods to prevent hypotension.  It was found that vasopressor is widely used in most research with incidence of hypotension varied from 4%-87,4%. IVCU studies reported the incidence of hypotension in 15,3%-43%. Leg Elevation a non-invasive technique studies reported the incidence of hypotension in 33,3-41,4%. Injection speed adjustment methods resulted incidence of hypotension in Fast injection 50 %-75% and Slow Injection in 36,7%-61%. In addition, granisetron methods diluted in normal saline reported the incidence of hypotension in 17,5%-42%. Low dose spinal anesthesia studies reported incidence of hypotension in 0% - 62,9%. Discussion. From all the research that has been reviewed, vasopressor (Phenylephrine), Leg Elevation and low dose spinal anesthesia could become primary options to prevent hypotension during spinal anesthesia in caesarean section since its effective to prevent hypotension, cost effective, and easy to applied in every medical facility.